Pungutan Zakat Profesi Pegawai Negeri Sipil (PNS) di Kota Palembang - Umar Hamdan; Ahmad Syathiri; Ahmad Maulana; Efva Octavina D.G (Falah: Jurnal Ekonomi Syariah, 2018)
The importance of professional zakat development is also one of the government's efforts to increase the source of state income other than taxes and create synergy between tax and zakat. Along with the development of the Islamic economy which is the solution to the economic development of the Ummah, the professional zakat can be used as a source of funding to be distributed for the welfare of the community. The purpose of this study was to determine the capacity of the ability to pay professional civil service zakat. The method of data collection is done by distributing random questionnaire to 200 civil servants from various agencies that live in the city of Palembang. Data analysis was carried out based on descriptive analysis. The results of the study show that civil servants have a great potential to be collected income zakat.